2015
DOI: 10.1016/j.molimm.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells: Versatile gatekeepers of pain

Abstract: Mast cells are important first responders in protective pain responses that provoke withdrawal from intense, noxious environmental stimuli, in part because of their sentinel location in tissue-environment interfaces. In chronic pain disorders, the proximity of mast cells to nerves potentiates critical molecular cross-talk between these two cell types that results in their synergistic contribution to the initiation and propagation of long-term changes in pain responses via intricate signal networks of neurotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 91 publications
1
77
0
3
Order By: Relevance
“…Stimulated MCs secrete vasoactive and proinflammatory mediators, such as the preformed heparin, histamine, serotonin, proteases (e.g., tryptase), and TNF, as well as the de novo synthesized leukotrienes, prostaglandins, and cytokines (IL-1, IL-6, IL-8, TNF). At least histamine, prostaglandin D 2 (PDG 2 ), and tryptase are known to stimulate sensory nerves and elicit pain (Dai et al, 2004;Chatterjea and Martinov, 2015). In addition, histamine, PGD 2 , IL-6, TNF, and tryptase could also stimulate microglia, as well as CRH release from the hypothalamus (Turnbull and Rivier, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated MCs secrete vasoactive and proinflammatory mediators, such as the preformed heparin, histamine, serotonin, proteases (e.g., tryptase), and TNF, as well as the de novo synthesized leukotrienes, prostaglandins, and cytokines (IL-1, IL-6, IL-8, TNF). At least histamine, prostaglandin D 2 (PDG 2 ), and tryptase are known to stimulate sensory nerves and elicit pain (Dai et al, 2004;Chatterjea and Martinov, 2015). In addition, histamine, PGD 2 , IL-6, TNF, and tryptase could also stimulate microglia, as well as CRH release from the hypothalamus (Turnbull and Rivier, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical mediators released from mast cells through degranulation activate nociceptors that can conversely release mediators to activate mast cells when injured [28,29] . When compared to wild-type (WT) mice, mast cell-deficient mice exhibit hypo-responsive hind paws in the presence of heat and mechanical stimulus [30] . The mast cell-dependent nociceptive response has been reported to be related to histamine signaling [31] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MCs may be involved in FMS (Lucas et al, 2006;Pollack, 2015) as well as other comorbid conditions (Theoharides, 2013a). MCs have been increasingly associated with inflammation (Galli et al, 2008;Theoharides et al, 2012a) and pain (Heron and Dubayle, 2013;Chatterjea and Martinov, 2015). The number of MCs was significantly increased in the papillary dermis of FMS patients (Blanco et al, 2010).…”
Section: Pathogenesismentioning
confidence: 99%